Updated System Supporting Regional Development in Germany - Alexander Kotov (Научно-аналитический вестник Института Европы РАН, 2021)
The long-term trajectory of the German regional policy is formed by the terms of overcoming the consequences of the coronavirus pandemic. The article discusses in this context the comprehensive all-German system for financing structurally weak regions, provides information on specific programs in 2020–2021, and also shows the connection with European instruments for financing regional policy in 2021–2027. The restructuring of this system of support measures was designed to improve the situation in underdeveloped territories and to help reduce differences in the conditions of recent challenges in technology, energy, and ecology. It is determined that Germany continues to be characterized by the differentiation in terms of economic potential between the East and West of the country. The paper demonstrates that the pandemic only highlighted the demands for the development of new mechanisms and a more active regional policy. It is emphasized that all eligible regions in the country now have access to more than 20 funding programs that were previously restricted to the regions of East Germany. It is determined that the streamlining of such measures is clearly only an auxiliary function in the public administration system and is aimed, first of all, at better coordination of existing instruments. Efficiency limitations are also the continuing autonomy of many programs, the possibility of excessive competition from now all underdeveloped regions of Germany for financial resources.